1974
DOI: 10.1113/jphysiol.1974.sp010615
|View full text |Cite
|
Sign up to set email alerts
|

The effects of load and force on tremor at the normal human elbow joint

Abstract: SUMMARY1. Spontaneous flexion-extension tremor of the elbow was recorded in normal human subjects while they exerted a flexing force against different loads.2. Increases in the flexing force up to i or 3 of the subject's maximum were accompanied by increases in the amplitude of the tremor. A further increase to very large forces was associated with a decrease in tremor.3. When the subject flexed against a spring, the frequency of the tremor was related to the properties of the spring; with increasingly stiff s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
60
1
2

Year Published

1981
1981
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(74 citation statements)
references
References 14 publications
11
60
1
2
Order By: Relevance
“…Previous studies have shown that induced tremor increases as the level of muscle activity increases [Joyce and Rack, 1974;Manini et al, 2005;Matthews and Muir, 1980]. Thus the observed reduction in tremor cannot be related to the reduction in MVC.…”
Section: Tremor Amplitudementioning
confidence: 83%
See 1 more Smart Citation
“…Previous studies have shown that induced tremor increases as the level of muscle activity increases [Joyce and Rack, 1974;Manini et al, 2005;Matthews and Muir, 1980]. Thus the observed reduction in tremor cannot be related to the reduction in MVC.…”
Section: Tremor Amplitudementioning
confidence: 83%
“…Various studies have shown that self maintaining force fluctuations (hereafter referred to as instability) can be revealed when contracting against a compliant load, such as a spring, and can be attributed to instability of the stretch reflex pathway [Durbaba et al, 2005;Joyce and Rack, 1974;Lippold, 1970;Matthews and Muir, 1980]. Also, modelling and experimental studies have shown that the frequency of oscillation of the instability is linked to whether the short (spinal) or long (transcortical) latency pathway of the stretch reflex is predominantly activated [Brown et al, 1982;De Serres et al, 2002;Durbaba et al 2005Durbaba et al , 2013Lippold, 1970;Matthews and Muir, 1980;Stein and Oguztöreli, 1976].…”
Section: Introductionmentioning
confidence: 99%
“…However, when the frequency of the mechanical component of physiological tremor is reduced by increasing the mass loading of the limb (Joyce and Rack 1974;Brown et al 1982a), a component at 8 -12 Hz remains constant or even shifts to slightly higher frequencies (Elble and Randall 1976;Elble and Randall 1978), suggesting that it has a neural origin. There is a tendency for unfused or partially fused motor unit twitches to cause tremor and while the mean motor unit firing frequency is somewhat higher than the frequency of physiological tremor, there is a tendency for short-term clustering of firing in the range of 8 -12 Hz (Elble and Randall 1976;Elble and Koller 1990; see also Halliday et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…A number of sources of physiological tremor have been suggested, including mechanical resonance of the limb (Joyce and Rack 1974;Elble andRandall 1976, 1978;Brown et al 1982a;Burne et al 1984), synchronisation of motor unit firing (Elble and Randall 1976;Allum et al 1978;Marsden 1984;Elble and Koller 1990;Matthews 1997;Timmer et al 1998a,b; see also Halliday et al 1999) and instability within the stretch reflex arc (Lippold 1970(Lippold , 1971Young and Hagbarth 1980;Zahalak and Cannon 1983;Burne et al 1984;Young 1984, Graham andRedman 1993;Miao and Sakamoto 1997;Sakamoto et al 1998;Santillan et al 2003). The multifactorial nature of tremor was emphasised by Llinas who described it as an "emerging property of various components" (Llinas 1984, p.178).…”
Section: Introductionmentioning
confidence: 99%
“…Passive mass-spring systems, such as human limbs, oscillate at a resonant frequency that is inversely related to mass. The resonant frequency of the human arm is approximately 2-to 3-Hz (Joyce & Rack, 1974), and previous studies have revealed 3-Hz peaks in human arm tremor (Fox & Randall, 1970;Robson, 1962). Thus, mechanical resonance could contribute to the 2-to 3-Hz peaks observed in the present study.…”
Section: Sensitivity To Fatiguementioning
confidence: 99%